Legal Effectiveness of Issuing Land Rights Certificates in Palu City - Rahmia Rachman; Suarlan Suarlan; Erlan Ardiansyah (Universitas Widya Gama Malang, 2023)
This research aims to find out the role of land deed official in the issuance of land rights certificates in Palu City as well as the obstacles faced by land deed official in Palu City in the implementation of the process of issuing land rights certificates. This research uses Empirical Juridical methods through data collection techniques through in-person interviews with informants as well as through document collection. The result of this research is that land deed official Palu City has an important role in the issuance of land rights certificates in Palu City to realize guarantees of legal certainty and administrative order based on Government Regulation No. 24 of 1997 and National Land Agency Regulation No. 1 of 2006. Obstacles regarding the process of issuing land rights certificates faced by land deed official not only come from the public, but also from the government. Obstacles that come from the community include the lack of community understanding of land registration procedures, the community has difficulty meeting the requirements of land rights registration and land rights are difficult to account for legally. Obstacles derived from the government include lack of human resources in the land office in palu city and constraints regarding inadequate facilities.